Characterization of the radiation pattern of antennas via FDTD and time-domain moment expansion - Glaucio L. Ramos; Cássio G. Rego (Journal of Microwaves, Optoelectronics and Electromagnetic Applications, 2014)
An alternative method is proposed to characterize the radiation pattern of antennas from an impulse response, based on a moment expansion together with a frequency domain near-to-far-field transformation via a FDTD/CPML solver. The approach introduced in the present work is intended for printed antenna analysis in special cases when the geometries to be modeled require a high degree of discretization in the space-time domain, which directly affects the frequency resolution when using FFT to perform the conventional NF-FF techniques. Results are compared with those obtained by a reference frequency-domain NF-FF technique and the applicability of the proposed method is demonstrated.